Clinical patterns and outcomes of hospitalized patients with grinder-related neurovascular injuries: A decade of experience from a Level I Trauma center - Hassan Al-Thani (440106) (2024)
Background Occupational injuries impose a substantial global burden, affecting millions of workers annually, which demands urgent attention to enhance workplace safety and health standards. We aimed to outline the frequency, patterns of injury, and clinical characteristics of patients injured by high-rotation cutting tools (grinders) and to pinpoint the neurovascular (nerves and blood vessels) injuries. Methods A retrospective study was conducted and included all adult patients hospitalized because of grinder-related injuries at the only level I Trauma Center in the country. The characteristics of patients, mechanism of injury, management and outcomes were analyzed based on the anatomical location of injuries. Results 127 patients were hospitalized with grinder-related injuries over ten years. The incidence of GRIs showed an increasing trend over the years. All patients were males with a mean (SD) age of 34.9 (9.8) years. The majority were general laborers (66.1 %), injured by portable grinders (86.6 %), and direct blade contact (64.6 %). The median Injury Severity Score (ISS) was 5.0(IQR 4.0–9.0), and the median Glasgow Coma Scale (GCS) at ED was 15 (3–15). The most frequently injured part was the upper extremity (36.2 %), followed by the lower extremity (33.9 %) and the face (27.6 %). One-third of cases had vascular injuries, and 23.6 % had nerve injuries. Suturing was done for all patients; repairs and debridements were performed in 62 % and 58 % of cases, respectively, and 21 % required vascular surgery. Amputations were required in 9.4 % of cases. Thirty patients had nerve injuries involving the median (11 %) and radial (9.4 %) nerves. Among patients who had neurovascular injuries, 30 % (12/40) experienced complications during the hospital stay, while 60 % (24/40) ended up with physical disabilities. Conclusion Individuals affected by power-tool accidents were predominantly young males, mainly general laborers, with a significant proportion being expatriates. The trend of grinder-related injuries increases over time, with portable grinders being a primary source of injuries due to direct contact with the blade. The anatomical injuries mainly include fractures of the upper and lower extremities. Further studies are warranted to understand the cultural aspects and training requirements of workers handling power tools, aiming to achieve sustainable injury prevention effectively. Other Information Published in: Injury License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.injury.2024.111914